The burden of thalassemia in Punjab: A roadmap forward - Amrith Mathew; Praveen C. Sobti (Pediatric Hematology Oncology Journal, 2017)
β-thalassemia is one of the commonest monogenic disorders in India and Punjab is significantly impacted with an estimated 4700 patients with thalassemia major. Like several other states in India with a high prevalence of thalassemia, Punjab is confronted with the fact that the magnitude of the problem is poorly defined, and there is no clear roadmap for thalassemia control within the context of a National Thalassemia Control Program. There is a paucity of clinical research in the state of Punjab with respect to the incidence, prevalence, morbidity and mortality related to thalassemia, and this project is intended to generate exact data with regards to the above. This article looks at a “Project Rainbow”, a potential strategy by which the Central and Punjab Governments, NGOs, Parents-Patients Societies and Corporate Houses can work together to intervene at each stage of the thalassemia care giving process and reduce the burden of Thalassemia in Punjab.